Apoptosis in pancreatic β-islet cells in Type 2 diabetes - Tatsuo Tomita (Biomolecules & Biomedicine, 2016)
Apoptosis plays important roles in the pathophysiology of Type 2 diabetes mellitus (T2DM). The etiology of T2DM is multifactorial, including obesity-associated insulin resistance, defective insulin secretion, and loss of β-cell mass through β-cell apoptosis. β-cell apoptosis is mediated through a milliard of caspase family cascade machinery in T2DM. The glucose-induced insulin secretion is the principle pathophysiology of diabetes and insufficient insulin secretion results in chronic hyperglycemia, diabetes. Recently, hyperglycemia-induced β-cell apoptosis has been extensively studied on the balance of pro-apoptotic Bcl-2 proteins (Bad, Bid, Bik, and Bax) and anti-apoptotic Bcl family (Bcl-2 and Bcl-xL) toward apoptosis in vitro isolated islets and insulinoma cell culture. Apoptosis can only occur when the concentration of pro-apoptotic Bcl-2 exceeds that of anti-apoptotic proteins at the mitochondrial membrane of the intrinsic pathway. A bulk of recent research on hyperglycemia-induced apoptosis on β-cells unveiled complex details on glucose toxicity on β-cells in molecular levels coupled with cell membrane potential by adenosine triphosphate generation through K+ channel closure, opening Ca2+ channel and plasma membrane depolarization. Furthermore, animal models using knockout mice will shed light on the basic understanding of the pathophysiology of diabetes as a glucose metabolic disease complex, on the balance of anti-apoptotic Bcl family and pro-apoptotic genes. The cumulative knowledge will provide a better understanding of glucose metabolism at a molecular level and will lead to eventual prevention and therapeutic application for T2DM with improving medications.